Occupational self-efficacy and career adaptability in undergraduates who have participated in MBKM program - Juanita, Rekha; Sumardi, Rizqi Angelika; Kaihatu, Veronica Anastasia Melany (Junal Ilmu Manajemen, 2024)
An internship experience can lead to an individual's confidence to perform work-related tasks, known as occupational self-efficacy. This belief will affect the individual's career adaptability, namely the individual's ability to adapt to career development, work transitions, and work problems, which in turn will help individuals deal with change and uncertainty in the world of work. One of the internship programs supported by the government is the Merdeka Belajar Kampus Merdeka program, more commonly referred to as MBKM. It aimed at increasing student competence through real work-related experiences, especially in internship and research schemes. This study aimed to determine the relationship between occupational self-efficacy and career adaptability in undergraduate MBKM program participants. Subjects in this study were collected using convenience sampling and obtained from 117 undergraduates who had participated in the MBKM program. A positive and significant relationship was found between occupational self-efficacy and career adaptability in undergraduate MBKM program participants with a total effect of 43.2%. Thus, the research hypothesis is accepted, namely that occupational self-efficacy affects career adaptability in undergraduate MBKM program participants.